Pure Aqueous Planar Microsupercapacitors with Ultrahigh Energy Density under Wide Temperature Ranges. (11th May 2022) - Song, Li; Dai, Chunlong; Jin, Xuting; Xiao, Yukun; Han, Yuyang; Wang, Ying; Zhang, Xinqun; Li, Xiangyang; Zhang, Shaohua; Zhang, Jiatao; Zhao, Yang; Zhang, Zhipan; et al.
Abstract: Currently, limited by factors such as low working voltage (≤1 V), poor temperature tolerance, and underutilization of electrolytes, pure aqueous symmetric planar microsupercapacitors (PMSCs) show unsatisfactory energy density under wide temperature ranges. To address these issues, a novel strategy is introduced to construct pure aqueous PMSCs with an ultrahigh energy density under wide temperature ranges through the development of high‐performance carbon nanotube‐MnO2 microelectrodes and high‐voltage aqueous polyacrylamide polyelectrolyte with exceptional temperature tolerance and redox‐enhanced function. Notably, the capacitance contribution of alizarin red S redox additives and the outstanding ability to withstand high voltage of polyacrylamide polyelectrolyte play the crucial roles in improving the electrochemical performance of PMSCs. As a result, the constructed microdevice achieves a record‐high working voltage of 2 V at temperatures from −15 °C to 100 °C and ultrahigh areal energy densities of 12.9 μWh cm –2 at −15 °C, 17.4 μWh cm –2 at room temperature and 24 μWh cm –2 at 100 °C, which are superior to those of previously reported pure aqueous PMSCs at the temperature. Meanwhile, it also shows good flexibility and excellent cycling stability (92.7% after 25 000 cycles at −15 °C and 81% after 20 000 cycles at 100 °C). Abstract : Pure aqueous planar microsupercapacitors are constructed through paring carbon nanotube‐MnO2 microelectrodes with a new aqueous polyacrylamide polyelectrolyte of exceptional temperature tolerance and redox‐enhanced function to deliver a record‐high working voltage of 2 V and ultrahigh areal energy densities of over 12.9 μWh cm −2 at temperatures from −15 °C to 100 °C.